2015
DOI: 10.1186/s12936-015-0676-5
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of dhfr and dhps molecular markers in Plasmodium falciparum in pregnant women of Nchelenge district, Northern Zambia

Abstract: BackgroundSulphadoxine-pyrimethamine (SP) is the recommended drug for intermittent preventive treatment in pregnancy (IPTp) in most African countries, including Zambia. However, malaria is still one of the leading causes of morbidity and mortality in pregnant women despite reports of greater than 50% of women taking at least two doses of SP in IPTp. Studies have shown that resistance to SP is associated with mutations in the dhfr and dhps gene of Plasmodium falciparum. This study examined the prevalence of dhf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
1
10
1
Order By: Relevance
“…The prevalence of malaria among 375 pregnant women in the study conducted in Nchelenge District between February and April 2013 by Siame et al was much lower than what was observed in the current study, 15.0 % by microscopy and 22.0 % by PCR [ 45 ]. The differences in the prevalence of malaria in the two studies could be attributed to a number of factors.…”
Section: Discussioncontrasting
confidence: 56%
“…The prevalence of malaria among 375 pregnant women in the study conducted in Nchelenge District between February and April 2013 by Siame et al was much lower than what was observed in the current study, 15.0 % by microscopy and 22.0 % by PCR [ 45 ]. The differences in the prevalence of malaria in the two studies could be attributed to a number of factors.…”
Section: Discussioncontrasting
confidence: 56%
“…We observed a high prevalence of S108N (83.8% -95.0%), C59R (49.3% -81.3%) and N51I (44.8% -73.3%) followed by the A437G (46.2% -54.2%) mutations, and eventually A613S, S436F and A581G were implicated. These findings are consistent with results reported in other settings in Africa [53,[80][81][82][83]. Similar to the report by Mockenhaupt and colleagues, we detected pfdhps-G581 and S613 among parasites from the same region in Ghana (Northern Region) [84].…”
Section: Plos Onesupporting
confidence: 93%
“…The more the mutations, the stronger the resistance. The Pfdhfr triple mutant (N51I + C59R + S108N) and Pfdhps double mutant (A437G + K540E) have been strongly associated with potential resistance in sub-Saharan Africa [912]. …”
Section: Introductionmentioning
confidence: 99%